2021
DOI: 10.2147/ccid.s267203
|View full text |Cite
|
Sign up to set email alerts
|

Updates and Best Practices in the Management of Facial Erythema

Abstract: Facial erythema is a common dermatologic complaint. There are many medical and procedure-based treatments to help reduce the appearance of unwanted facial redness. The authors review a variety of treatment options and techniques to reduce facial erythema and prominent facial veins including topical medical therapies, a variety of lasers, light- and energy-based devices as well as the use of neuromodulators and sclerotherapy. The benefits and potential pitfalls of each procedure modality are also highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 67 publications
0
8
0
4
Order By: Relevance
“…Indeed, the laser provides good penetration into the dermis, however high costs and the risk of rupture of vessels, especially superficial ones, make it unattractive. Overall, as elegantly discussed elsewhere [ 13 , 28 , 29 , 30 ], many different lasers can be utilized to successfully treat vascular lesions, however a 532 nm laser with the advent of efficient cutaneous cooling and lengthening of pulse duration makes this particular one less painful with a smaller probability of developing purpura compared to other ones. Indeed, a 532 nm laser has a higher absorption coefficient for oxyhemoglobin as compared to a 595 nm pulse dyed laser [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the laser provides good penetration into the dermis, however high costs and the risk of rupture of vessels, especially superficial ones, make it unattractive. Overall, as elegantly discussed elsewhere [ 13 , 28 , 29 , 30 ], many different lasers can be utilized to successfully treat vascular lesions, however a 532 nm laser with the advent of efficient cutaneous cooling and lengthening of pulse duration makes this particular one less painful with a smaller probability of developing purpura compared to other ones. Indeed, a 532 nm laser has a higher absorption coefficient for oxyhemoglobin as compared to a 595 nm pulse dyed laser [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an animal experiment, the main effects of intradermal injection of BTX on rosacea were as follows: (1) significantly reduced the expression of biomarkers of LL‐37 induced rosacea, such as KLK5, matrix metallopeptidase 9 (MMP9), and transient receptor potential ankyrin 2 (TRPV2); (2) By cleaving SNARE protein in mast cells, mast cell degranulation is directly blocked to improve skin erythema 13 . At present, there are many treatment options for rosacea erythema and flushing, including drugs and/or lasers or light and energy‐based devices 16 . BTX is an optional treatment for patients with rosacea refractory erythema and flushing.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to determine the etiology and patient goals of facial erythema. In addition, the need for joint treatment in order to achieve the expected results must be recognized 16 . Li et al 18 reported two cases of BTX combined with IPL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations